2011
DOI: 10.1007/s11269-010-9762-1
|View full text |Cite
|
Sign up to set email alerts
|

Crop Reference Evapotranspiration: A Discussion of the Concept, Analysis of the Process and Validation

Abstract: The study at first recalls the concept of "potential evapotranspiration" (PET), originally considered equal to the evaporation climatic demand; then, it reminds the steps of its progressive evolution toward the concept of "reference crop evapotranspiration" (ET 0 ) determined on irrigated grass. A physical analysis conducted on the evaporation process is subsequently reported to help clarifying the links between ET 0 and evaporation climatic demand. This analysis clearly demonstrates that the equivalence of ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…Other studies also found PT values far below 1.26 but within the range of our study, mainly for forests (e.g. Komatsu, 2005;Shuttleworth and Calder, 1979;Viswanadham et al, 1991;Eaton et al, 2001) but also for tundra (Eaton et al, 2001) or grassland sites (Katerji andRana, 2011) -see McMahon et al (2013) for an overview. Our results 15 and these studies demonstrate that the standard level of PT=1.26 is close to the upper threshold of evaporation and will overestimate Ep at most sites (Table 5).…”
Section: Estimation Of Key Ecosystem Parameters 10supporting
confidence: 85%
See 1 more Smart Citation
“…Other studies also found PT values far below 1.26 but within the range of our study, mainly for forests (e.g. Komatsu, 2005;Shuttleworth and Calder, 1979;Viswanadham et al, 1991;Eaton et al, 2001) but also for tundra (Eaton et al, 2001) or grassland sites (Katerji andRana, 2011) -see McMahon et al (2013) for an overview. Our results 15 and these studies demonstrate that the standard level of PT=1.26 is close to the upper threshold of evaporation and will overestimate Ep at most sites (Table 5).…”
Section: Estimation Of Key Ecosystem Parameters 10supporting
confidence: 85%
“…Lysimeter data, probably the most precise evaporation 5 measurements available, have been used (e.g. Pereira and Pruitt, 2004;Katerji and Rana, 2011;Yoder et al, 2005), but measurements are scarce and difficult to upscale to larger ecosystems. Pan evaporation data, available in larger volumes and at larger scales, have also been used (Donohue et al, 2010;Zhou et al, 2006;McVicar et al, 2012) but provide a proxy of open-water evaporation, rather than actual ecosystem potential evaporation, and also exhibit biases related to the location, shape and composition of the instrument (Pettijohn and Salvucci, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, ET 0 is a climatic parameter and can be computed from weather 53 data. ET 0 expresses the evaporating power of the atmosphere at a specific location and time of the 54 year and it allows for spatial and temporal comparisons, independently of different land cover types 55 and temporal coverage changes (Katerji and Rana, 2011). ET a will be less than or equal to ET 0 , but 56 never greater.…”
mentioning
confidence: 99%
“…The data of P and AED were obtained from CRU TS v.3.24.01 (Harris et al, 2014). The concept of the PET has proven to be inappropriate because the evaporation climatic demand is not only linked to the climate but also to the type of the evaporative surface, and some authors have adopted a more suitable term: evaporative atmospheric demand (Katerji and Rana, 2011;McVicar et al, 2012). However, we will keep the term "PET" throughout the text as the original data are named by the source.…”
Section: Identification Of Dry and Wet Conditionsmentioning
confidence: 99%